Crack path identification in a nanostructured pearlitic steel using atom probe tomography. (1st January 2018) - Leitner, T.; Sackl, S.; Völker, B.; Riedl, H.; Clemens, H.; Pippan, R.; Hohenwarter, A.
Abstract: Severely plastically deformed pearlitic steels often possess poor crack-growth resistance along the deformation-induced elongated nanolamellar microstructure. However, it is unknown if the crack propagates in the nanocrystalline ferrite or along the ferrite-cementite interface. Here, a pearlitic steel subjected to high pressure torsion exhibiting a fracture toughness of only ~ 4 MPa·m 1/2 along the elongated structure was selected to address this fundamental question. For the first time 3-dimensional atom probe tomography was employed to unravel the local atomistic fractography. We present clear evidence that the low fracture toughness is controlled by crack propagation along the interface between the nanocrystalline carbon-rich and ferritic phase. Graphical abstract: